2016
DOI: 10.1111/nph.14284
|View full text |Cite
|
Sign up to set email alerts
|

Exploring key cellular processes and candidate genes regulating the primary thickening growth ofMoso underground shoots

Abstract: The primary thickening growth of Moso (Phyllostachys edulis) underground shoots largely determines the culm circumference. However, its developmental mechanisms remain largely unknown. Using an integrated anatomy, mathematics and genomics approach, we systematically studied cellular and molecular mechanisms underlying the growth of Moso underground shoots. We discovered that the growth displayed a spiral pattern and pith played an important role in promoting the primary thickening process of Moso underground s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 59 publications
1
86
0
Order By: Relevance
“…By comparing corpus cell numbers among five bamboo species with different culm sizes, we found that although corpus cells, which develops to pith tissue (Wei et al ., ), were dramatically increased with the increase in culm size, and the ratio of corpus cell number to the square of culm diameter was exponentially decreased with the culm size increase (Figure g–i), somehow demonstrating that the increase in pith cells could not keep pace with the cross‐area increase. Thus, more pith cells should be reassigned to the cross area to fill the gap, highly possibly by decreasing pith cells across the internode.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By comparing corpus cell numbers among five bamboo species with different culm sizes, we found that although corpus cells, which develops to pith tissue (Wei et al ., ), were dramatically increased with the increase in culm size, and the ratio of corpus cell number to the square of culm diameter was exponentially decreased with the culm size increase (Figure g–i), somehow demonstrating that the increase in pith cells could not keep pace with the cross‐area increase. Thus, more pith cells should be reassigned to the cross area to fill the gap, highly possibly by decreasing pith cells across the internode.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for making paraffin section and light microscopy observation were same as described in Wei et al . (). The lengths of over 300 parenchymal cells in each 1‐cm part were measured.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations